2013
DOI: 10.1177/0300060513487643
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B surface antigen seroclearance in patients with chronic hepatitis B infection: A clinical study

Abstract: Objective: To investigate the clinical characteristics of hepatitis B surface antigen (HBsAg) seroclearance in patients with chronic hepatitis B virus (HBV) infection. Methods: Patients with chronic HBV infection who achieved sustained virological response (SVR) within 6 years of ceasing formal antiviral treatment were assessed for HBsAg seroclearance (defined as loss of serum HBsAg on repeated testing for a period of >6 months), using enzyme immunoassays. Phase of HBV infection and liver function (serum alani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…In CHB patients, loss of hepatitis B surface antigen (HBsAg) is strongly associated with good clinical outcome . Because HBsAg is one of the subviral replication products of covalently closed circular DNA (cccDNA), the intrahepatic reservoir for HBV, HBsAg serves as a surrogate marker for cccDNA and, thus, for HBV‐infected cells …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In CHB patients, loss of hepatitis B surface antigen (HBsAg) is strongly associated with good clinical outcome . Because HBsAg is one of the subviral replication products of covalently closed circular DNA (cccDNA), the intrahepatic reservoir for HBV, HBsAg serves as a surrogate marker for cccDNA and, thus, for HBV‐infected cells …”
Section: Introductionmentioning
confidence: 99%
“…Although with HBsAg loss there is still a lifetime of intrahepatic persistence of entire, episomal, replication‐competent HBV genomes and detectable HBV DNA in the liver, with phases of undetectable and very low but detectable HBV DNA in serum, the loss is associated with (i) normalization of alanine aminotransferase (ALT) levels, (ii) gain of anti‐HBS over time which does not indicate immunity of any type, (iii) reduction in liver necroinflammation, (iv) increased likelihood of liver fibrosis regression, (v) substantially reduced risk of liver cirrhosis, decompensation and hepatocellular carcinoma, if there is no cirrhosis or superinfection with hepatitis C virus or hepatitis D virus at the time of HBsAg clearance, and (vi) increased survival . Given the limitations of current therapies, HBsAg loss is considered the closest thing we currently have to a cure for CHB and is now referred to as a “functional cure” . Because of the high natural hepatitis B early antigen (HBeAg) reversion rate, the high relapse rate after treatment and the high rate of mixed infection with wild‐type virus or core/precore mutant viruses and growing prevalence of HBeAg‐negative disease, the combination of HBsAg loss and HBV DNA suppression is now considered the most important endpoint for clinical trials and the ultimate short‐term goal of treatments with the currently available medications …”
Section: Introductionmentioning
confidence: 99%
“…HBsAg loss with or without development of anti-HBs is by far the most valuable surrogate marker for treatment end point. Loss of HBsAg correlates well with prevention of complications like cirrhosis and HCC [20-22]. …”
Section: Current End Points Of Hbv Treatmentmentioning
confidence: 99%
“…Recent studies have shown that serum HBsAg titres strongly correlate with intrahepatic cccDNA levels , and several authors have proposed that HBsAg quantification may be a useful marker to monitor IFN treatment . Serum HBsAg levels tend to be higher in HBeAg‐positive than in HBeAg‐negative patients and also differ according to HBV genotype.…”
Section: Importance Of Hbsag Lossmentioning
confidence: 99%